Entrepreneurship : Halwamanis / Nor Atiqah Saliman ... [et al.] - Saliman, Nor Atiqah; Mohamad Afandi, Madihah; Mislin, Nur Zawany; Che Johari, Siti Zainab; Mamat@ Mohamad, Hafsah (2009)
This business plan serves to develop the financial, administrative, marketing and operation plan. The business plan addresses many challenging and opportunities as new companies that will be operate in January 2010. But, to fulfill this situation, we had done our plans like what stated above.